PENERAPAN METODE ACTIVITY BASED COSTING DALAM MENENTUKAN HARGA POKOK PRODUKSI (STUDI KASUS PADA PENGRAJIN SANDAL DESA BERBEK) - Bariyah, Binti Ro’isatul; Hwihanus, Hwihanus (JEA17: Jurnal Ekonomi Akuntansi, 2020)
ABSTRACTThis study aims to determine how to apply the calculation of activity based costing in determining the cost of goods manufactured and how to compare the cost of goods manufactured using traditional methods and activity based costing methods. This study used descriptive qualitative method. The data used are qualitative data in the form of company identity and quantitative data related to the company's production costs. Data collection was carried out by observation and interviews.The results showed the calculation of the cost of goods manufactured at UD. Karimunjawa Perkasa with the traditional method compared to the activity based costng method gives lower results for the mountain slop sandals and mountain slop sandals, while for the flat sandals gives a greater result. This is due to the calculation of the cost of goods manufactured by the traditional method using one cost driver while the activity based costing method uses more than one cost driver. Charging using activity based costing makes the calculation of the cost of goods manufactured more accurate, thus helping management in making decisions and determining the selling price